Pengembangan Manajemen Pangan Berkelanjutan Disulawesi Tengah: Analisis Strategi Branding dan Teknologi untuk Meningkatkan Daya Saing - Zulkifli Zainuddin; Tohiroh Tohiroh; Agung Laksono Putra; Ummi Kultsum (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Access to safe food is a basic right guaranteed by Article 27 paragraph (2) of the 1945 Constitution, which states that every citizen has the right to a decent living. In Indonesia, including Central Sulawesi, food availability is threatened by population growth, making food security a crucial aspect that must be maintained. However, food challenges are not limited to availability, which remains a problem in several regions. The purpose of this study is to analyze and develop sustainable food management in Central Sulawesi through a qualitative approach using SWOT analysis techniques. The research method used is a qualitative approach aimed at exploring in-depth aspects of branding strategy and technology utilization in developing sustainable food management. Data collection was conducted through in-depth interviews, direct observation, focus group discussions (FGDs), and qualitative data analysis to obtain comprehensive information from various stakeholders. This information was then integrated into a SWOT analysis of branding strategy and technology utilization to increase the competitiveness of local food products in domestic and international markets. This approach allows researchers to develop recommendations based on empirical field context. This research found that communities have many external opportunities. They are expected to take several steps, including leveraging policy support to improve access to financing, leveraging digital technology to address branding and marketing limitations, and promoting product certification with the support of government regulations.